A comprehensive exploitation of instance selection methods for automatic text classification - Washington Luiz Miranda da Cunha (2024)
Progress in Natural Language Processing (NLP) has been dictated by the rule of more: more data, more computing power, more complexity, best exemplified by the {Large Language Models. However, training (or fine-tuning) large dense models for specific applications usually requires significant amounts of computing resources. Our focus here is an under-investigated data engineering (DE) technique, with enormous potential in the current scenario – Instance Selection (IS). The IS goal is to reduce the training set size by removing noisy or redundant instances while maintaining or improving the effectiveness (accuracy) of the trained models and reducing the training process cost. In this sense, the main contribution of this Ph.D. dissertation is twofold. Firstly, we survey classical and recent IS techniques and provide a scientifically sound comparison of IS methods applied to an essential NLP task - Automatic Text Classification (ATC). IS methods have been normally applied to small tabular datasets and have not been systematically compared in ATC. We consider several neural and non-neural SOTA ATC solutions and many datasets. We answer several research questions based on tradeoffs induced by a tripod: effectiveness, efficiency, reduction. Our answers reveal an enormous unfulfilled potential for IS solutions. Furthermore, in the case of fine-tuning the transformer methods, the IS methods reduce the amount of data needed, without losing effectiveness and with considerable training-time gains. Considering the issues revealed by the traditional IS approaches, the second main contribution is the proposal of two IS solutions: E2SC, a novel redundancy-oriented two-step framework aimed at large datasets with a particular focus on transformers. E2SC estimates the probability of each instance being removed from the training set based on scalable, fast, and calibrated weak classifiers. We hypothesize that it is possible to estimate the effectiveness of a strong classifier (Transformer) with a weaker one. However, as mentioned, E2SC focuses solely on the removal of redundant instances, leaving other aspects, such as noise, that may help to further reduce training, untouched. Therefore, we also propose biO-IS, an extended framework built upon our previous one aimed at simultaneously removing redundant and noisy instances from the training. biO-IS estimates redundancy based on E2SC and captures noise with the support of a new entropy-based step. We also propose a novel iterative process to estimate near-optimum reduction rates for both steps. Our final solution is able to reduce the training sets by 41% on average (up to 60%) while maintaining the effectiveness in all tested datasets, with speedup gains of 1.67 on average (up to 2.46x). No other baseline, was capable of scaling for datasets with hundreds of thousands of documents and achieving results with this level of quality, considering the tradeoff among training reduction, effectiveness, and speedup.